A child with anhidrosis, pan-analgesia and self-mutilation: a unique peripheral neuropathy - Palit, A.; Inamadar, A.C.; Pandit, V.S.; Desai, V.C.; Lagali, S.S. (European Journal of Pediatric Dermatology, 2012)
Congenital insensitivity to pain with anhidrosis is a rare hereditary peripheral neuropathy. The children with this disorder since birth subsequently develop the self-mutilating behavior which dominates the clinical picture following dentition. With increasing age, mental retardation becomes evident and mobility predisposes them to develop painless fractures, traumatic wounds and accidental burn. Here is reported an Indian child with this unique peripheral neuropathy. These patients require multi-speciality care and dermatologists are involved in the management of anhidrosis as well as cutaneous trophic changes.